Globalization and knowledge management in projects - Dagmara Bubel (Foundations of Management, 2015)
Knowledge management is a field of management dealing with the use of knowledge, methods, and tools to effectively coordinate complex and unique projects. In accordance with this definition, project knowledge can be treated as a useful resource of information that allows projects to be implemented in compliance with its objectives: time, costs, and quality of results. Knowledge in the activity of an organization, including in the implementation of projects, has for many years been an area of interest to researchers, who confirmed its key importance for building permanent competitive advantages of companies and enterprises. In project management, this issue takes on a new character, as it is transferred to the field of dynamic, time restricted, temporary, and team-implemented projects. The aim of this paper is to present the results of a survey regarding the use of practices of knowledge management in projects in international organizations and to show that the concept of knowledge management in projects is a tool conducive to spreading the process of globalization.
Keywords: 650; globalization; knowledge management; projects